Growing Fashion Consciousness; A Threat to Environment - Arif, Abdur Rehman; Khan, Arman; Jabbar, Shumaila; Pirzado, Ali Akbar; Syeda, Alle; Khan, Waseem (The journal of contemporary issues in business and government, 2021)
The Study stands on an assumption that growing fashion consciousness leads towards a general change oriented behavior and so escort towards an intense consumption pattern. To fulfill that huge demand of all kinds, massive industrialization takes place, which is evidently a threat to the environment. Study ascertains the fashion consciousness of only the most neglected segment of the market to establish that people are getting fashion conscious to a threatening level. This study identifies the fashion information sources, shopping preferences and in particular, measures the fashion consciousness of the underappreciated segment as mature female consumers in Pakistan. A comprehensive questionnaire is exposed to the females aging 45 to onwards who were explained with every question in order to ensure the validity of the instrument. It is found that mature women are fashion conscious but not as much as they share information of fashion. Mature women are more concerned about comfort than style and more concerned about style than brand name, which is a clear evidence of lack of advertisement and focus of businesses on this wealthy and independent segment. Even then, they are fashion conscious and acquire fashion information through catalogues, store display, fashion shows, asking family members, and social gatherings. This amplifying fashion consciousness leads to a change oriented behavior in general. People seek change in everything around (even before it expiries) which will obviously generate innovative demands and in result, industrialization will be at its peak; an obvious threat to the environment.